2013
DOI: 10.1387/ijdb.120087fp
|View full text |Cite
|
Sign up to set email alerts
|

The internal structure of embryonic gonads and testis development in Drosophila melanogaster requires scrib, lgl and dlg activity in the soma

Abstract: Interest in the mechanism leading to the formation of the germline and its differentiation during Drosophila development, initiated even as soon as the first ever cloned tumour suppressor gene in Drosophila, the lethal (2) giant larvae (lgl), had been identified. Further work has shown that the lgl, as well as discs large-1 (dlg) and scribble (scrib) tumor suppressor genes code for scaffolding proteins associated with either the cytoskeletal matrix or the septate junctions that act in common pathways in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…scrib is expressed in the somatic gonadal cells of the newly formed embryonic Drosophila gonads [101,102] and analysis of agametic gonads and pseudo-gonads made of aggregated germ cells confirmed this observation [102]. Analysis of scrib and dlg mutant gonads revealed that the gonadal mesodermal cells are not able to extend projections between the germ cells suggesting a role in establishing the intimate contacts of the gonadal mesoderm to the germ cells [93,102]. At larval stages, dlg, scrib and lgl expression in the somatic lineage is indispensable for testis homeostasis and spermatogenesis, as depletion of these genes results in extremely small testes with reduced number of GSCs, increased number of early cyst cells (positive for early cyst cell marker Traffic-Jam), impaired differentiation and infertility.…”
Section: Cyst Stem Cells and Somatic Cyst Cells: The Supportive Cellsmentioning
confidence: 77%
See 4 more Smart Citations
“…scrib is expressed in the somatic gonadal cells of the newly formed embryonic Drosophila gonads [101,102] and analysis of agametic gonads and pseudo-gonads made of aggregated germ cells confirmed this observation [102]. Analysis of scrib and dlg mutant gonads revealed that the gonadal mesodermal cells are not able to extend projections between the germ cells suggesting a role in establishing the intimate contacts of the gonadal mesoderm to the germ cells [93,102]. At larval stages, dlg, scrib and lgl expression in the somatic lineage is indispensable for testis homeostasis and spermatogenesis, as depletion of these genes results in extremely small testes with reduced number of GSCs, increased number of early cyst cells (positive for early cyst cell marker Traffic-Jam), impaired differentiation and infertility.…”
Section: Cyst Stem Cells and Somatic Cyst Cells: The Supportive Cellsmentioning
confidence: 77%
“…All these studies on the role of septate junction components in the Drosophila testis, underline the importance of the CySCs and SCCs to encapsulate the germline and establish the cyst integrity, which is necessary for germline differentiation and normal testis function to finally produce healthy sperm and ensure fertility [10,89,93]. Interestingly, the Drosophila testis cyst cells show striking similarities with the Sertoli cells, the supportive cells of the mammalian germline, in terms of cytoskeletal and scaffolding components [10].…”
Section: Cyst Stem Cells and Somatic Cyst Cells: The Supportive Cellsmentioning
confidence: 98%
See 3 more Smart Citations